Dampak Rasio Keuangan, Peran Arus Kas Sebagai Variabel Moderating, Harga Saham Industri Properti: Pengaruh Current Ratio, Return On Equity, Debt to Equity, Earning Per Share Terhadap Harga Saham Industri Properti Dan Peran Arus Kas Sebagai Variabel Moderasi - Manik, Tasya; Haris , Abdul (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this research is to examine (1) various elements that can influence the share prices of companies listed on the Indonesia Stock Exchange (BEI) and (2) whether free cash flow affects the share prices of property companies listed on the BEI. From 2018 to 2022; and (3) Do Current Ratio, Return On Equity, Debt to Equity Ratio, Earning Per Share, and Cash Flow simultaneously influence property company share prices on the IDX? and (4) Financial reports for 2018–2022 from eleven companies listed on the IDX are used as secondary data and samples.Method: Sampling was carried out purposively, and multiple linear regression analysis was used with the SPSS application to explain the data. Research and data analysis show that EPS has a significant effect and influences share prices, and several variables influence share prices positively or negatively. Likewise, free cash flow moderates the DER and EPS variables compared to share prices. The conclusion and implication of this research is that EPS has a positive and significant effect on stock prices. Furthermore, the mediation results show the Sig DER value and the Sig EPS value on share prices, which means that cash flow significantly moderates DER and moderates EPS on share prices.